Significant contributing causes of cancer deaths among Hispanics in Colorado, USA, 1983-1992 - Kimberley Sweitzer; Lorann Stallones
Cancer deaths in the state of Colorado, U.S.A., totaled 53,921 between 1983 and 1992. Death certificates for this period were used to evaluate Hispanic cancer deaths by contributing causes of death and primary occupation of the decedent. The relative risks for diabetes and liver disease as contributing causes of death were significantly higher among Hispanics when compared to non-Hispanics who had also died of cancer (RR for diabetes = 1.90; 95% C.I. (1.64,2.19) and RR for liver disease = 1.44; 95% C.I. (1.23,1.68)). Hispanics who had died of cancer were significantly less likely to have drug abuse as a contributing cause of death when compared to non-Hispanics (RR for drug abuse = 0.69; 95% C.I. (0.52,0.91)). Laborers, service workers, and clerical workers who were Hispanic, were significantly more likely to die of cancer with either diabetes or liver disease as a contributing cause of death than were non-Hispanics in the same occupational category (p<0.05). Chronic diseases, such as diabetes and liver disease, may be reducing the survivability of cancer among Hispanics.